Measuring Poverty in Latin America and the Caribbean : Methodological Considerations When Estimating an Empirical Regional Poverty Line - Castaneda, R. Andres; Gasparini, Leonardo; Garriga, Santiago; Lucchetti, Leonardo R.; Valderrama, Daniel (World Bank, Washington, DC, 2016)
This paper contributes to the methodological literature on the estimation of poverty lines for country poverty comparisons in Latin America and the Caribbean. The paper exploits a unique, comprehensive data set of 86 up-to-date urban official extreme and moderate poverty lines across 18 countries in Latin America and the Caribbean, as well as the recent values of the national purchasing power parity conversion factors from the 2011 International Comparison Program and a set of harmonized household surveys that are part of the Socio-Economic Database for Latin America and the Caribbean project. Because of the dispersion of country-specific poverty lines, the paper concludes that the value of a regional poverty line largely depends on the selected aggregation method, which ends up having a direct impact on the estimation of regional extreme and moderate poverty headcounts.